Long-term effects of air pollution on daily outpatient visits for allergic conjunctivitis from 2013 to 2020: a time-series study in Urumqi, China - Liu, Dongwei; Gui, Siyu; Wang, Xinchen; Wang, Qianqian; Qiao, Jianchao; Tao, Fangbiao; Tao, Liming; Jiang, Zhengxuan; Yi, Xianglong (Frontiers in Public Health, 2024)
Introduction: This study aimed to elucidate the effects of outdoor air pollution and allergic conjunctivitis and population-based lagged effects of air pollution. Methods: We included data on six major air pollutants, PM10, PM2.5, carbon monoxide (CO), sulfur dioxide (SO2), nitrogen dioxide (NO2), and ozone (O3), and 3325 allergic conjunctivitis outpatient visits in Urumqi, northwest China, from 1 January 2013 to 31 December 2020. We developed quasi-Poisson generalized linear regression models with distributed lagged nonlinear models (DLNM), and single and multi-pollutant models were constructed to investigate single-day and cumulative lagged effects in detail. Results: Our results confirmed that elevated PM10 and NO2 levels are significantly associated with increased allergic conjunctivitis outpatient visits with lags of 2 and 3 days respectively, and subgroup analyses further suggest that the effects of PM10 and NO2 on allergic conjunctivitis are more pronounced during the warm season. Women are more sensitive to PM10 exposure and the effect of air pollution on allergic conjunctivitis is influenced by age (e.g., infancy and older people). Discussion: Our work provides the first time-series study in Urumqi, the world's furthest inland city from the ocean. Further implementation of specific outdoor air pollution controls such as the burning of fossil fuels like coal, as well as special population protection policies remain necessary. Multicenter studies with larger sample sizes are needed.